Influence of roasting conditions on health-related compounds in different nuts. (1st August 2015) - Schlörmann, W.; Birringer, M.; Böhm, V.; Löber, K.; Jahreis, G.; Lorkowski, S.; Müller, A.K.; Schöne, F.; Glei, M.
Highlights: Five different nut varieties were roasted under different conditions. The influence of roasting on health-related compounds was determined. Antioxidant capacity and sensory properties were analysed. When TBARS and acrylamide increased, antioxidant capacity and tocopherols decreased. Moderate roasting preserves constitutional compounds and sensory properties. Abstract: Due to their health-beneficial ingredients the consumption of nuts can contribute to a healthy diet. The composition of hazelnuts, almonds, macadamia nuts, pistachios and walnuts regarding health-promoting and potentially harmful compounds was examined before and after roasting under different time and temperature conditions. Fatty acid compositions were not affected by roasting. Malondialdehyde increased with higher roasting temperatures (17-fold in walnuts). Levels of tocopherol isomers were reduced after roasting (α-T: 38%, β-T: 40%, γ-T: 70%) and hydrophilic antioxidant capacity decreased significantly in hazelnuts (1.4-fold), macadamia nuts (1.7-fold) and walnuts (3.7-fold). Increasing roasting temperatures supported the formation of significant amounts of acrylamide only in almonds (1220 μg kg −1 ). In general, nuts roasted at low/middle temperatures (120–160 °C) exhibited best sensory properties. Therefore, desired sensory quality along with a favourable healthy nut composition may be achieved by roasting over a low to medium temperature range.